A Nineteenth Century Ottoman Gentleman's Cookbook - Işın, Priscilla Mary (Petits Propos Culinaires, 1999)
The author, who lives in Istanbul and spends most of her spare time in the libraries there, recently edited in a handsome paperback edition the Turkish book which is the subject of this essay. The book (ISBN 975-363-825-6) is entitled A?ç?ba??, by Mahmud Nedimbin Tosun, and is published by YKY. Their address is given in a note at the very end of the essay, together with information about price and ordering. The book, published in 1900, was written by a Turkish officer, Mahmud Nedim bin Tosun who wrote his book with attention to detail and to appeal to the inexperienced cook.